2013
DOI: 10.1111/pace.12030
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intracardiac Echocardiography during Atrial Fibrillation Ablation

Abstract: As the volume and complexity of catheter ablation of atrial fibrillation (AF) continue to rise, there is increasing attention directed at reducing exposure to ionizing radiation. This has led to the emergence of intracardiac echocardiography (ICE) as a stand-alone imaging modality guiding AF ablation. In addition to directing transseptal puncture, ICE may be used to identify left atrial structures and to guide the manipulation of catheters. ICE may also be used to visualize the esophagus in real-time and to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 20 publications
1
50
0
1
Order By: Relevance
“…Studies examining alternative imaging techniques for leftsided ablations have become more prominent lately due to the development of 3D electroanatomic mapping and catheter navigation software [4][5][6][7][8][9][10]. These alternative or adjunctive modalities may increase procedure time and cost and additionally carry their own risks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies examining alternative imaging techniques for leftsided ablations have become more prominent lately due to the development of 3D electroanatomic mapping and catheter navigation software [4][5][6][7][8][9][10]. These alternative or adjunctive modalities may increase procedure time and cost and additionally carry their own risks.…”
Section: Discussionmentioning
confidence: 99%
“…While use of this technology is an intriguing method to further decrease fluoroscopy exposure, the inability to visualize the transseptal sheath or dilator prior to advancement of the needle raises concerns about the safety of this technique. ICE is frequently used as an alternative imaging modality for TSP in adult atrial fibrillation ablations [6,7,10]. ICE catheters allow for visualization of puncture and early recognition of pericardial effusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracardiac echocardiography was performed using a 10F probe Acunav (Siemens Medical Solution distributed by Biosense Webster) or 10F probe SoundStar (Biosense Webster, Inc., Diamond Bar, CA), advanced through a percutaneous femoral vein access [10,11]. These catheters are equipped with a linear-phased array multi-frequency (5.5 to 10 MHz) transducer and connected to Vivid I system (GE Healthcare, USA) or Cypress system (Acuson Corp, Mountain View, CA).…”
Section: Intracardiac Echocardiographymentioning
confidence: 99%
“…Previous studies reported the usefulness of intracardiac echocardiography (ICE) during AF ablation to identify left atrial structures, to guide the manipulation of catheters and to support the early identification of procedural complications [9,10]. In this study, we investigated the usefulness of ICE to optimize the manipulation of nMARQ TM catheter during AF ablation.…”
Section: Introductionmentioning
confidence: 99%